Foreign language learning can improve response inhibition in individuals with lower baseline cognition: Results from a randomized controlled superiority trial - Grossmann, Judith Alina; Aschenbrenner, Steffen; Teichmann, Birgit; Meyer, Patric (Frontiers in Aging Neuroscience, 2023)
Introduction The world’s population is aging, increasing the prevalence of dementia. Recently, foreign language learning in later life has been suggested to improve cognition and thus support healthy cognitive aging. To date, however, there are only a few studies with conflicting findings. Therefore, the purpose of this study was to examine whether learning a foreign language can improve executive attention and executive functions in healthy older adults. Additionally, we sought to identify factors affecting cognitive change in foreign language learners, such as cognitive reserve, previous foreign knowledge and usage, and global cognition at baseline. Methods In a randomized-controlled trial, we assigned 34 monolinguals between the ages of 65 and 80 to a language learning or a waiting list control group. The participants enrolled in a Spanish course for beginners that met five days a week for 1.5 h for a total of 3 weeks. The waiting list control group received no intervention but had the opportunity to join the language training at the end of the study. All participants underwent an assessment of executive attention (primary outcome), executive functions, verbal fluency, and attention (secondary outcomes) before, immediately after the course, or after a waiting period of 3 weeks for the control group and 3 months after the course or the waiting period. Results Foreign language learning did not significantly improve primary or secondary outcomes, neither immediately nor 3 months after the course. However, moderation analyses revealed that participants with lower global baseline cognition tended to improve more on response inhibition than individuals with higher baseline cognition. This relationship was not evident in the waiting list control group. Discussion Our results suggest that studying a foreign language does not generally improve executive attention or executive functioning. Nevertheless, individuals with poorer baseline cognition may benefit cognitively from foreign language learning in response inhibition, a domain particularly affected by cognitive aging. Our findings highlight the need of focusing dementia prevention efforts on groups that are more vulnerable to cognitive decline. Additionally, more individualized approaches, including utilizing technology-assisted learning, might enable participants to practice at their performance level, increasing the likelihood of discernible cognitive gains. Clinical trial registration https://drks.de/search/en, identifier DRKS00016552.